The Loss of Oral Traditions in the Far East Russia: Future of the Community - Chuguevskaia, Anastasiia Stepanovna (2017)
This paper investigates the issues threatening the existence of oral traditions and expressions, a strong element of Intangible Cultural Heritage of indigenous nations in Russian Federation and discusses the consequences for the associated communities of such threats. Two of the major threats, rapid globalisation and modernisation of human life-style, have led to the distancing between generations, a phenomenon clearly evident in native settlements where younger generations are moving to urban areas and abandoning their native culture. This paper specifically focuses on the case of Evenks people of Russia, who represent one of the largest native minorities of the country. The Evenks were chosen to be a representation of the phenomenon due to the fact that the native community shows high concern for the issue of oral traditions endangerment and works on safeguarding it. The research used content analysis and netnography research to collect data from social media associated with Evenks and research articles on the issue to study the factors that affect the loss of oral traditions and the consequences for Evenks people of the loss of their oral heritage. It was found that topic of the endangerment of oral traditions among Evenks lacks the diversity of research, and does not receive enough support of legal protection of oral traditions and expressions. Nonetheless Evenks people show a great case of community empowerment through the process of creating programs for safeguarding their language and culture in the modern setting. Este artículo investiga los problemas que amenazan la existencia de tradiciones y expresiones orales, un elemento fuerte del Patrimonio Cultural Inmaterial de las naciones indígenas en la Federación de Rusia y discute las consecuencias para las comunidades asociadas de tales amenazas. Dos de las principales amenazas, la rápida globalización y la modernización del estilo de vida humano, han llevado al distanciamiento entre generaciones, fenómeno que se manifiesta claramente en los ...